Clinical case of mixed infection of Viral hepatitis E and Infectious mononucleosis - A. L. Bondarenko; K. G. Korobicyn; Yu. P. Slobozhaninova (Детские инфекции (Москва))
The article considers a case from clinical practice: mixed infection of viral hepatitis E and infectious mononucleosis caused by Epstein-Barr virus in a boy of 15 years. The patient was long observed by a pediatrician with a diagnosis of lacunar tonsillitis, hospitalized on the 10th day of the disease in an infectious diseases hospital with a preliminary diagnosis of infectious mononucleosis. Objectively, in addition to acute tonsillitis, detected polylithionite, hepatosplenomegaly. The biochemical analysis of blood revealed a pronounced cytolysis syndrome, a study on the markers of viral hepatitis (revealed anti-HEV IgM). Discharged on the 28th day of the disease with residual effects.